2019
DOI: 10.3390/w11112319
|View full text |Cite
|
Sign up to set email alerts
|

Gully Erosion Susceptibility Mapping Using Multivariate Adaptive Regression Splines—Replications and Sample Size Scenarios

Abstract: Soil erosion is a serious problem affecting numerous countries, especially, gully erosion. In the current research, GIS techniques and MARS (Multivariate Adaptive Regression Splines) algorithm were considered to evaluate gully erosion susceptibility mapping among others. The study was conducted in a specific section of the Gorganroud Watershed in Golestan Province (Northern Iran), covering 2142.64 km2 which is intensely influenced by gully erosion. First, Google Earth images, field surveys, and national report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 96 publications
3
13
2
Order By: Relevance
“…Splitting the database resulted in non-linear connections between the humus and the studied elements; thus, the MARS algorithm having no assumptions on distribution on the input data was more successful with better performance ( Figure 5 ). Better performance of MARS had been proven in other studies too [ 69 , 70 ], and we also found it an effective prediction tool and, in this case, a technique for better exploration of relationships among different variables.…”
Section: Resultssupporting
confidence: 73%
“…Splitting the database resulted in non-linear connections between the humus and the studied elements; thus, the MARS algorithm having no assumptions on distribution on the input data was more successful with better performance ( Figure 5 ). Better performance of MARS had been proven in other studies too [ 69 , 70 ], and we also found it an effective prediction tool and, in this case, a technique for better exploration of relationships among different variables.…”
Section: Resultssupporting
confidence: 73%
“…SE is a natural geomorphological process (erosion, transport and sedimentation) but after human disturbances can be considered as a land degradation one, which has been a recurring challenge for decades over the world for stakeholders, and especially, in countries such as Iran. Recently, scientists have examined land degradation indicators including desertification 42 , deforestation 43 , salinization 44 , alkalization of soils 45 , overgrazing 46 , intensive land-use changes 47 , and especially, water and wind erosion 48 , 49 . Many of these studies integrated remote sensing, Geographic Information System (GIS) and the RUSLE approach for the estimation of SE 50 – 55 .…”
Section: Introductionmentioning
confidence: 99%
“…Javidan et al, [19] applied GIS (Geographic Information System) techniques and the MARS (Multivariate Adaptive Regression Splines) algorithm to evaluate gully erosion susceptibility mapping in a specific section of the Gorganroud Watershed in Golestan Province (Northern Iran), covering 2142.64 km 2 . They also used Google Earth images and field surveys in combination with national reports to generate a map consisting of 307 gully-headcut points.…”
Section: Summary Of This Special Issuementioning
confidence: 99%